A porous metal–organic framework with a unique hendecahedron-shaped cage: structure and controlled drug release. Issue 9 (4th February 2016) - Wei, Lian-Qiang; Chen, Qing; Tang, Li-Le; Zhuang, Chong; Zhu, Wen-Run; Lin, Ning
Abstract : A porous MOF with [Cu2 (COO)4 ] SBU was constructed from tricarboxylic acid ligand and pyrazine, which features a unique hendecahedron cage-liked cavity with good stability and a high BET surface, showing good controlled drug release properties of ibuprofen over anethole and guaiacol. Abstract : A porous MOF constructed from a [Cu2 (COO)4 ] secondary building unit, H3 L (H3 L = [1, 1′;3′, 1′′]terphenyl-4, 5′, 4′′-tricarboxylic acid), and pyrazine ligands features a unique hendecahedron cage-like cavity with good stability and a high BET surface area of 3235 m 2 g −1, showing good controlled drug release property of ibuprofen over those of anethole and guaiacol.